EXPLORING THE IMPACT OF HIP-HOP PEDAGOGY ON STUDENT ENGAGEMENT AND LEARNING OUTCOMES - Bagas Aditya Putra; Soeprijanto; Daryanto (Global Synthesis in Education Journal, 2024)
The increasing reliance on LMS for delivering educational content necessitates an evaluation framework to ensure its effectiveness in meeting educational goals. The CIPP model provides a comprehensive approach to evaluate various aspects of LMS utilization. The primary objectives are to evaluate the contextual relevance, resource adequacy, implementation processes, and outcomes of LMS usage in educational settings. This study employs a mixed-method approach, utilizing the CIPP evaluation checklist for data collection, supplemented by semi-structured interviews, document analysis, and observations. The population includes students and educators using the LMS, with a representative sample selected for detailed analysis.  The research results of Context evaluation revealed that the LMS aligns well with institutional educational goals and user needs. The Input phase highlighted sufficient technical and support resources, though some gaps in training were identified. The Process evaluation indicated high user engagement but pointed out areas for improvement in system usability. Finally, the Product evaluation showed positive outcomes in terms of user satisfaction and achievement of educational objectives, though continuous improvements are needed to maintain effectiveness. This research provides valuable insights into the strengths and weaknesses of LMS implementation, guiding future enhancements for better educational outcomes.